If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6m + -6 + -2 = 22 Reorder the terms: -6 + -2 + 6m = 22 Combine like terms: -6 + -2 = -8 -8 + 6m = 22 Solving -8 + 6m = 22 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 6m = 22 + 8 Combine like terms: -8 + 8 = 0 0 + 6m = 22 + 8 6m = 22 + 8 Combine like terms: 22 + 8 = 30 6m = 30 Divide each side by '6'. m = 5 Simplifying m = 5
| (4z+7)/(z-19)=415/(5z-95) | | 7a-2+7a=12 | | 5a^2-2ab-16b^2= | | 31-x=43 | | -p+3p=-2 | | 42=5(x+8) | | -6x+1-6=1 | | 21y-49= | | .05x+.33-.75x+0.6666666667-0.8333333333x=8-1.4 | | 3.18-4=8.72 | | 2/3s=18 | | 11-10x=42x+19 | | 6x+11=-79-9 | | x+3/4=-1/2 | | x/(-1/6)=6/7 | | 4a-1=2a+27 | | 3x^2+2=59 | | X-15=3x | | x/-1/6=5/7 | | x/-1/6+6/7 | | 1.6s=-8 | | 6(4h-3)=3(5h-3) | | 0.1a-1.09=0.91 | | (1/2)(6x+7)=3x | | -11-6x=-9x | | 1/2z-3/5=12/5 | | 60m=60 | | 13j-4=9j+52 | | 3/5x=7(1-x) | | -79=-5+2(-x-15) | | 3x^3+6x^2+5x=27 | | 2m+1=3m-2 |